2020
DOI: 10.3390/s20164640
|View full text |Cite
|
Sign up to set email alerts
|

Application of Artificial Neural Networks for Accurate Determination of the Complex Permittivity of Biological Tissue

Abstract: Medical devices making use of radio frequency (RF) and microwave (MW) fields have been studied as alternatives to existing diagnostic and therapeutic modalities since they offer several advantages. However, the lack of accurate knowledge of the complex permittivity of different biological tissues continues to hinder progress in of these technologies. The most convenient and popular measurement method used to determine the complex permittivity of biological tissues is the open-ended coaxial line, in combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The obtained results are an indication that the proposed approach is robust and can be used to retrieve the dielectric properties of materials with the OECP technique. When this study is compared with the previously reported work in the literature, to the best of authors' knowledge, only one reported work carried out a study utilizing NN to retrieve complex permittivity with OECP response [21]. However, the reported study only used measurements; therefore, train and test data were restricted with the measurements and [24] 111.8 109.23 6.9 5.26 42.00 42.9 3.68±0.03 Methanol [26] 33.64 37.01 5.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The obtained results are an indication that the proposed approach is robust and can be used to retrieve the dielectric properties of materials with the OECP technique. When this study is compared with the previously reported work in the literature, to the best of authors' knowledge, only one reported work carried out a study utilizing NN to retrieve complex permittivity with OECP response [21]. However, the reported study only used measurements; therefore, train and test data were restricted with the measurements and [24] 111.8 109.23 6.9 5.26 42.00 42.9 3.68±0.03 Methanol [26] 33.64 37.01 5.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, an artificial neural network model is proposed in [21] to compute the complex permittivity from the measured reflection coefficients for biomedical applications. In the proposed study [21], 102 experiment samples including standard liquids and biological tissues were measured in order to train, validate and test the neural network model. Prediction accuracy of ±5% was obtained for the complex permittivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the analysis methods of complex dynamical networks have played an important role in the big data transmissions, information processing and power grid (Baran & Rzysko, 2020;Bonello et al, 2020;Chen et al, 2019;Ding et al, 2019;Hernandez-torres et al, 2020;Wang et al, 2019). Recently, the networked control technology brings many conveniences to industrial development and technological advancements (Chen et al, 2020;Hu et al, 2017;Zou, Wang, Dong et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%